Price undertakings, VERs, and foreign direct investment: The case of foreign rivalry - Jota Ishikawa; Kaz Miyagiwa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
Antidumping (AD) petitions are often withdrawn in favor of VERs and price undertakings. We compare foreign firms' incentive to engage in foreign direct investment (FDI) under a VER and a price undertaking, with special emphasis on foreign rivalry. We show that a VER is less likely to induce FDI than a price undertaking or AD. Thus, the importing country can increase the level of protection by replacing an AD duty with a VER. This may account for the GATT ban on VERs, given the proliferation of AD cases during the 1990s.
Keywords: F1; 330; FDI; price undertakings; antidumping; VER; WTO; Auslandsinvestition; Antidumping; Exportbeschränkung; WTO-Recht; Internationale Geschäftsbeziehungen; Außenwirtschaftstheorie; Theorie